1984
DOI: 10.1111/j.1600-0897.1984.tb00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of Pregnancy on the Development of Experimental Allergic Encephalomyelitis in Rabbits

Abstract: In the present study we have investigated the influence of pregnancy on the induction and development of experimental autoimmune encephalomyelitis (EAE) in rabbits in relation to the time of gestation. Randomly bred rabbits were immunized with encephalitogenic bovine brain homogenate in complete Freund's adjuvant before or during pregnancy. The appearance of EAE was delayed and occurred only after delivery, abortion, or fetal resorption. The incidence of the disease was lower and the duration longer. The level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…A number of studies support the hypothesis that the increased female susceptibility to autoimmune disease is largely due to effects mediated by estrogen (34 -36). However, it is well known that pregnancy levels of estrogen are immunosuppressive and protect against a number of experimental autoimmune disorders including collagen-induced arthritis (37,38) and EAE (16,17). To explain this apparent dichotomy, it has been proposed that the response to estrogen is biphasic, with basal levels of hormone leading to conditions favoring autoimmunity and pregnancy levels of hormone associated with protection from autoimmune disease (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies support the hypothesis that the increased female susceptibility to autoimmune disease is largely due to effects mediated by estrogen (34 -36). However, it is well known that pregnancy levels of estrogen are immunosuppressive and protect against a number of experimental autoimmune disorders including collagen-induced arthritis (37,38) and EAE (16,17). To explain this apparent dichotomy, it has been proposed that the response to estrogen is biphasic, with basal levels of hormone leading to conditions favoring autoimmunity and pregnancy levels of hormone associated with protection from autoimmune disease (23).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, sex hormones have been found to alter the disease course in the EAE model system. Pregnancy has been shown to protect animals from EAE (16,17), and estrogen administered at levels equal or greater than those found during pregnancy have been shown to suppress the clinical and histopathological symptoms of EAE in mice and rats (18,19). Recent studies have found that estriol (E3), a hormone produced by the placenta during pregnancy, had profound effects on EAE (20), and, based on these results, human trials using E3 to treat MS patients have begun.…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…In view of the fact that the enzyme converting testosterone into estradiol, aromatase, is present in several cells and tissues it remains to be shown whether testosterone exerts its anti-inflammatory effect directly or through conversion in the female sex hormone. Gender differences in susceptibility to and severity of EAE have also been known for many years ( [71,162,244]). …”
Section: Estrogens and Multiple Sclerosismentioning
confidence: 99%
“…Pregnancy has been shown to suppress the development of EAE (22,23), and estrogen administered at levels equal to or greater than those in pregnancy have been shown to diminish clinical disease (24,25). In recent studies from our laboratory, ovariectomy and loss of endogenous estrogen enhanced the severity of EAE, whereas treatment of mice with estrous and diestrous levels of exogenous estrogen effectively suppressed EAE (26,27).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%